BECOMING THE MAIN PILLAR OF ORGANISATIONAL SUCCESS: A LITERATURE REVIEW ON THE INTEGRATION OF VISIONARY LEADERSHIP, HUMAN RESOURCE MANAGEMENT STRATEGIES, AND ORGANISATIONAL CULTURE THAT PROMOTES OPTIMAL PERFORMANCE AND SUSTAINABILITY - Ignatius Septo Pramesworo (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study examines the integration of visionary leadership, human resource management (HRM) strategies, and organisational culture as key pillars in driving optimal performance and organisational sustainability. Through a systematic literature review approach, this study examines concepts, theories, and previous research findings that link these three elements in the context of modern, adaptive, and competitive organisations. The results of the study show that visionary leadership plays an important role in providing strategic direction and motivation, while HR strategies focus on developing competencies and empowering employees in synergy with the organisation's vision. In addition, a strong organisational culture that integrates sustainability values supports consistency and innovation in achieving long-term goals. This research provides conceptual and practical contributions as a basis for developing a holistic organisational management model capable of addressing the dynamic challenges in today's global business environment.